The Effect Of Burning Time On The Amount Of Bacteria Staphylococcus Aureus Contamination Of Grilled Meatballs Sold In Darusssalam, Banda Aceh - Novita, Andi; Ismail, Ismail; Khoirunnisa, Fathonah; Ferasyi, Teuku Reza; Darniati, Darniati; Zainuddin, Zainuddin (The Faculty of Veterinary Medicine of Syiah Kuala University, 2023)
This study aims to determine the effect of heating time in the combustion process on Staphylococcus aureus contamination in grilled meatballs. A total of 9 samples of meatballs obtained from 3 sellers of grilled meatballs were divided into 3 treatments, namely burning at temperatures ranging from 56C-59C for 1 minute, 3 minutes, and 5 minutes, with 3 repetitions. Determination of the number of microbes was carried out using the Total Plate Count (TPC) method. The research data were analyzed using a two-way ANOVA analysis of variance followed by Duncan's test. The results showed that the duration of burning affected the amount of Staphylococcus aureus contamination in grilled meatballs. The best combustion was shown at 5 minutes, with a microbial count of 3.6 101 CUF/g. The results of the analysis of variance (ANOVA) showed that there was a significant difference (P0.05) in the average value of Staphylococcus aureus microbial contamination in grilled meatballs given treatment. Based on the calculation results, it can be concluded that 5 minutes of burning time is the most effective for decontaminating the amount of Staphylococcus aureus microbial contamination in grilled meatballs.